IL-17A inhibitors alleviate Psoriasis with concomitant restoration of intestinal/skin microbiota homeostasis and altered microbiota function - Zhao, Huixia; Shang, Lili; Zhang, Yuting; Liang, Zhaojun; Wang, Nan; Zhang, Qian; Gao, Chong; Luo, Jing (Frontiers in Immunology, 2024)
Background: Disturbed gut microbiota and associated metabolic dysfunction exist in Psoriasis.Despite the growing use of interleukin-17 inhibitor (anti-IL17) therapy, the effect of anti-IL17 on gut/skin microbiota function is not fully understood in patients with Psoriasis.Objective: Therefore, we explored whether Psoriasis is associated with alterations in selected gut/skin microbiota in a study cohort, and a longitudinal cohort study to reveal the effects of IL-17A inhibitor treatment on gut microbiota in Psoriasis.In a case-control study, 14 patients with Psoriasis and 10 age, sex and body mass indexmatched Healthy Controls were recruited. Longitudinal mapping of the gut microbiome was performed using 16S rRNA gene sequencing. Mouse models were used to further study and validate the interrelationship between the skin microbiome and the gut microbiome in Psoriasis. PICRUST2 was applied to predict the function of the bacterial community.In Psoriasis patients, gut microbiota dysbiosis was present with increased heterogeneity:decreased Bacteroidota and increased Firmicutes as well as Actinobacteriota predominating in Psoriasis. Escherichia-Shigella enrichment was associated with reduction in serum levels of total bile acid and markers in Apoptotic pathways. After IL-17A inhibitor treatment in Psoriasis patients, longitudinal studies observed a trend toward a normal distribution of the gut microbiome and modulation of apoptosis-related metabolic pathways. Results from a mouse model showed dysregulation of the skin microbiota in Psoriasis characterized by Staphylococcus colonization.The psoriatic gut/skin microbiota exhibits loss of community stability and pathogen enrichment. IL-17A inhibitors restore microbiota homeostasis and metabolic pathways, reduce proinflammatory cytokine expression, and alleviate symptoms in patients with Psoriasis.